1, 3, 5‐Trinitroperhydro‐1, 3, 5‐triazine (RDX)‐Based Sheet Explosive Formulation with a Hybrid Binder System. Issue 2 (18th January 2016) - Jangid, Suresh Kumar; Singh, Mrityunjay Kumar; Solanki, Vasant Jadavji; Talawar, Mahadev Bhimappa; Nath, Tribhuvan; Sinha, Rabindra Kumar; Asthana, Srinandan
Abstract: A plastic‐bonded explosive (PBX) in the form of a sheet was formulated comprising of 1, 3, 5‐trinitroperhydro‐1, 3, 5‐triazine (RDX) and an hybrid binder system containing a linear thermoplastic polyurethane and a fluoroelastomer (Viton). The effect of a fluoroelastomer on the explosive as well as mechanical properties and thermal behavior of sheet explosive formulations were investigated and compared with a control formulation containing 90 % of RDX and 10 % of natural rubber (ISNR‐5). The replacement of 10 % natural rubber by a hybrid binder system led to an increase in the velocity of detonation (VOD) of the order of 250–950 m s −1 and better mechanical properties in terms of tensile strength (1.9–2.5 MPa) compared to the control formulation (RDX/ISNR‐5 (90/10)). The compatibility of ingredients and thermal decomposition kinetics of selected sheet explosive formulations were investigated by vacuum stability tests and differential scanning calorimetry (DSC). The results suggested better compatibility of RDX with the hybrid binder system (polyurethane/Viton), which is useful to reduce potential hazards in handling, processing, and storage. Abstract :